The Relationship between International and Domestic Law in the Field of Attribution of Responsibility to a State in International Investment Disputes - Amidimehr, Elham; Seifi, Jamal (Public Law Researsh, 2021)
The attributability of actions to states within the context of investment treaty disputes and to focus on the roles played by international and domestic laws in such attributions have caught the attention of jurists in recent years. The ILC Draft Articles on Responsibility of States for Internationally Wrongful Acts, and particularly, article 3 points to the main outcome of this debate, where it does not consider domestic law irrelevant in internationally wrongful acts and stipulates that the issue is subject to international law and it will take into account the relevance of domestic law. Thus, although the characterization of an act of a State as internationally wrongful is an independent function of international law and such characterization is not affected by the characterization of the same act as lawful by domestic law, it does not mean that domestic law is irrelevant to such description; on the contrary, it may be related in various ways. The present article attempts to examine the challenging junction of domestic and international law with regard to the attributability of actions taken within the framework of investment treaties, specifically by state-owned and para-statal entities that exercise elements of state authority. قابلیت انتساب عمل به دولت در چارچوب اختلافات معاهده‌ سرمایه‌گذاری و تمرکز بر نقش‌هایی که حقوق بین‌الملل و حقوق داخلی در چنین انتسابی ایفا ‌می‌نمایند در زمره‌ مباحثی است که در سال‌های اخیر بسیار مورد ‌توجه حقوقدانان بوده و ماده 3 مواد کمیسیون حقوق بین‌الملل در ارتباط با مسئولیت دولت‌ها نیز بیانگر پیامد اصلی این بحث است که فی‌الواقع، حقوق داخلی را با مسأله متخلفانه بودن اعمال از حیث بین‌المللی بی‌ارتباط تلقی ‌ننموده، بلکه مقرر ‌می‌دارد مسئله مورد بحث، تابع حقوق بین‌الملل است لیکن حقوق بین‌الملل نیز خود تا حدِ ارتباط، حقوق داخلی را در نظر خواهد گرفت. بنابراین اگرچه توصیف خصوصیات یک عمل به عنوان عملی غیرقانونی از عملکردهای مستقل حقوق بین‌الملل است که تحت ‌تأثیر توصیف خصوصیات این عمل بموجب حقوق داخلی قرار نمی‌گیرد لیکن این گفته بدین معنی نیست که حقوق داخلی با توصیف عمل متخلفانه‌ بین‌المللی بی‌ارتباط ‌است؛ بالعکس، ممکن ‌است به طرق مختلفی به آن مرتبط‌ باشد. در این مقاله سعی بر‌ آن است که تلاقی چالش‌برانگیز حقوق داخلی و حقوق بین‌الملل در بحث قابلیت انتساب اعمال ‌صورت ‌گرفته در چارچوب معاهدات سرمایه‌گذاری توسط ارگان‌های دولتی و نهادهای نیمه‌دولتی که عناصر اختیارات دولتی را اعمال می‌نمایند مورد واکاوی قرار‌ گیرد.
Keywords: Attribution; Domestic Law; International Arbitration; International Investment Treaties; International Law; حقوق بین‌الملل; حقوق داخلی; داوری بین‌المللی; معاهدات سرمایه‌گذاری بین‌المللی; کلیدواژگان انتساب مسئولیت

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم